Null phenotype non-Hodgkin Lymphoma presenting as a large chest wall mass: case report - Sekkate, Sakina (The African Field Epidemiology Network, 2012)
Tumors of chest wall represent a variant entity. Most of them arise from metastasis of malignant tumors or from local invasion by contiguity. However, non-Hodgkin's lymphomas of the chest wall are extremely rare; only a few cases have been reported in the literature. We report a case about a Moroccan woman, with non-Hodgkin null phenotype lymphoma of the chest, treated successfully with CHOP (cyclophosphamide, Doxorubicin, Vincristin and prednisone) followed by local radiotherapy.